Posted by **Kimba** on Sunday, January 3, 2010 at 12:37am.

(2x^3)-(14x^2)+12x=0

x=?

- Algebra -
**drwls**, Sunday, January 3, 2010 at 8:05am
First, factor out the common 2x.

This leaves you with

2x[x^2 -6x +6) = 0

x=0 is one solution. The others are the two roots of

x^2 -6x +6 = 0,

which are not integers. You can compute them with the quadratic equation

x = [6 +/- sqrt(12)]/2 = 3 +/- sqrt3

## Answer this Question

## Related Questions

- algebra - solve the following equation by clearing fractions show all work want ...
- algebra - solve the following equation by clearing fraction want to know if this...
- math - how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 ...
- Please check Algebra - Please take a look at my work and let me know if I made ...
- math - which equation is equivalent to 5x-2(7x+1)=14x? why? a -9x-2=14x b -9xt1=...
- algebra1 - could you walk-through the steps to solving this problem because I am...
- Algebra 1 - 1) what is the simplified form of (x-2)(2x+3)? Use the distributive...
- math - The rectangle given has a perimeter of 14 units. Find the value(s) of x ...
- algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...
- algebra 117b - Are these factorable Beecause I tried and could figure it out can...